The intraoperative gap differences due to joint distraction force differences in total knee arthroplasty are affected by preoperative lower limb alignment and body mass index. (October 2022) - Sameshima, Shin; Inui, Hiroshi; Taketomi, Shuji; Yamagami, Ryota; Kono, Kenichi; Kawaguchi, Kohei; Kage, Tomofumi; Tanaka, Sakae
Abstract: Background: Soft tissue balance is important for a good clinical result in total knee arthroplasty. Nevertheless, the appropriate evaluation of the intraoperative gap has not been established. We investigated the relationship between physical characteristics and gap differences due to distraction force, in order to determine whether intraoperative adjustment of the distraction force can be considered based on the physical characteristics of the patient. Methods: A total of 115 varus knees in which primary total knee arthroplasty was performed were retrospectively evaluated. The component gaps were measured under 60 and 80 N. The gap difference under 60 and 80 N was calculated. We performed a linear regression analysis to determine the correlation between the gap differences and patient parameters. Findings: Each gap was significantly larger under 80 N than under 60 N. The component gap difference is larger in the lateral compartment than in the medial compartment at each knee flexion angle. The gap difference negatively correlated with preoperative hip–knee–ankle angle at a knee flexion of 0° and 120° ( r  = −0.21, −0.19; p  = 0.02, 0.05) and positively correlated with BMI in the lateral compartment at a knee flexion of 90° ( r  = 0.31, p  < 0.001). Interpretation: The difference in the intraoperative gap due to the joint distraction force was affected by the preoperative HKA axis angle and the body mass index in the lateral compartment. Surgeons should consider the effect of preoperative limb alignment and body mass index in interpreting intraoperative gap measurement. Highlights: We measured the gap under two distraction force in total knee arthroplasty. We investigated the factor that affect the gap difference due to distraction force. The gap difference in the lateral compartment was affected by two patient factors. Hip Knee Ankle angle positively correlated in lateral gap at knee flexion 0 degree. The body mass index negatively correlated in lateral gap at knee flexion 90 degree.